2019
DOI: 10.3390/genes10050351
|View full text |Cite
|
Sign up to set email alerts
|

De Novo Assembly and Comparative Transcriptome Profiling of Anser anser and Anser cygnoides Geese Species’ Embryonic Skin Feather Follicles

Abstract: Geese feather production and the quality of downy feathers are additional economically important traits in the geese industry. However, little information is available about the molecular mechanisms fundamental to feather formation and the quality of feathers in geese. This study conducted de novo transcriptome sequencing analysis of two related geese species using the Illumina 4000 platform to determine the genes involved in embryonic skin feather follicle development. A total of 165,564,278 for Anser anser a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…As a large modular network, MAPK pathway regulates multiple physiological processes including the cell growth and differentiation (Junttila et al 2008). And the interactions of MAPK signaling play a crucial role in the keratinocyte differentiation, which can also adjust the skin homeostasis to maintain the various functions of the epidermis (Schmidt 2001). Previous studies had indicated that MAPK signaling pathway is widely required in various aspect of hair, feather, and wool follicles cycle and morphogenesis in cashmere goat (Yuan et al 2013), Pekin duck (Chen et al 2017), Tibetan sheep , and mice (Akilli Öztürk et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…As a large modular network, MAPK pathway regulates multiple physiological processes including the cell growth and differentiation (Junttila et al 2008). And the interactions of MAPK signaling play a crucial role in the keratinocyte differentiation, which can also adjust the skin homeostasis to maintain the various functions of the epidermis (Schmidt 2001). Previous studies had indicated that MAPK signaling pathway is widely required in various aspect of hair, feather, and wool follicles cycle and morphogenesis in cashmere goat (Yuan et al 2013), Pekin duck (Chen et al 2017), Tibetan sheep , and mice (Akilli Öztürk et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the most important secreted genes during feather follicle initiation and development are members of the inhibitors of Wnt signaling, including WIF1 and their receptors, including Frizzled 6 (FZD6), which were also detected as significantly regulated genes in the DEGs dataset. Several studies have argued that many of the DEGs that contribute to the Wnt signal pathway are present in the dorsal tissues of geese from various breeds and at different embryonic days [ 15 , 16 , 17 ]. The Wnt signaling is known to play a crucial role in regulating follicle formation in the developing avian skin [ 42 ], and is the major pathway that regulates the patterning of skin and controls how adult and embryonic stem cells decide which cell lineages to adopt for the skin and its appendages, in addition to regulating differentiated skin cells activities [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…With the progressive understanding of the developmental process of feather follicles, more and more new key regulatory factors are being uncovered in addition to the signals mentioned above. The advent of next-generation sequencing (NGS) has become a powerful tool to uncover the molecular signaling involved in the formation of feather follicles for feather maturation [ 15 , 16 , 17 , 18 , 19 , 20 ]. While the feather follicles of chickens and ducks are increasingly well studied, geese, as poultry with extremely high down feather quality, have been relatively seldomly studied.…”
Section: Introductionmentioning
confidence: 99%
“…Wnt signaling is very crucial for feather follicle development. The previous studies have suggested that there are a lot of DEGs in geese dorsal tissues across embryonic days and in different breeds ( Liu, et al, 2020 ; Liu, et al, 2018 ; Lowe, et al, 2015 ; Sello, et al, 2019 ) and these DEGs participate in the Wnt, BMP, MAPK, and Notch pathways. With the advancement of genetic engineering techniques, such as gene knockout and gene location mutation, it has been confirmed that the Wnt signaling pathway plays a key regulatory role during feather follicle development ( Andl, et al, 2002 ; Liu, et al, 2020 ; Xie, et al, 2020a ).…”
Section: Discussionmentioning
confidence: 99%